2008
DOI: 10.1038/ismej.2007.118
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and biogeochemical evidence for ammonia oxidation by marine Crenarchaeota in the Gulf of California

Abstract: Nitrification plays an important role in marine biogeochemistry, yet efforts to link this process to the microorganisms that mediate it are surprisingly limited. In particular, ammonia oxidation is the first and rate-limiting step of nitrification, yet ammonia oxidation rates and the abundance of ammoniaoxidizing bacteria (AOB) have rarely been measured in tandem. Ammonia oxidation rates have not been directly quantified in conjunction with ammonia-oxidizing archaea (AOA), although mounting evidence indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
475
11
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(556 citation statements)
references
References 63 publications
66
475
11
4
Order By: Relevance
“…deep waters (2956 m) of the Japan Sea (Nakagawa et al, 2007). Furthermore, these deep-sea genotypes are distinct from those that have been recovered from the upper 650 m of the water column at GB and Carmen Basins (Beman et al, 2008). These GB gene sequences are 497% similar to one another and 92.3 to 93.4% similar to N. maritimus.…”
Section: Species-resolved Transcriptomics Of Ammonia Oxidation Genesmentioning
confidence: 67%
“…deep waters (2956 m) of the Japan Sea (Nakagawa et al, 2007). Furthermore, these deep-sea genotypes are distinct from those that have been recovered from the upper 650 m of the water column at GB and Carmen Basins (Beman et al, 2008). These GB gene sequences are 497% similar to one another and 92.3 to 93.4% similar to N. maritimus.…”
Section: Species-resolved Transcriptomics Of Ammonia Oxidation Genesmentioning
confidence: 67%
“…A number of recent studies suggest that AOA dominate in marine habitats (Wuchter et al, 2006;Mincer et al, 2007;Beman et al, 2008). In contrast, Mosier and Francis, (2008) found that copies of b-proteobacterial amoA were two orders of magnitude higher than archaeal amoA in high-salinity estuarine sediments.…”
Section: Introductionmentioning
confidence: 89%
“…These clones are from several depths throughout the water column, but OTUs are identified only once in the data set using the previously published priority scheme (Cram et al, 2014a). Environmental parameters (from Beman et al, 2008;Cram et al, 2014a) are summarized in Supplementary Table S1.…”
Section: Data Sourcementioning
confidence: 99%